Distributed Temperature/Vibration Fiber Optic Sensor With High Precision and Wide Bandwidth - Tao He; Yanli Ran; Tao Liu; Hao Li; Cunzheng Fan; Wei Zhou; Zhijun Yan; Deming Liu; Qizhen Sun (IEEE Photonics Journal, 2019)
Distributed fiber optic sensor for multi-parameter measurements plays a crucial role in various applications. In this work, distributed temperature/vibration fiber optic sensor with high precision and wide bandwidth is proposed and experimentally demonstrated. To improve the signal-to-noise ratio (SNR) and sensitivity of the system, the backscattering enhanced optical fiber (BEOF) is employed to provide strong and stable sensing signal. With the assistance of the coherent phase detection, a high precision measurement of phase can be achieved. In addition, the wavelet packet decomposition algorithm is put forward to effectively discriminate the quasi-static temperature and dynamic vibration signals. In the experiment, wide bandwidth vibration signal from 0.01 Hz to 20 kHz can be successfully detected. Owing to the high sensitivity of the system, the local temperature change within the range of only 10 cm can be captured with high precision of 0.095 °C. Besides, the system has a good capability of fast response to the external temperature variation where the response time is around 0.3 seconds, which is meaningful for the early warning of centimeters-level sized fire source in the special oil and gas pipelines monitoring applications.